Pragmatic linguistic analysis of the videos by terrorists of the Barcelona and Cambrils attacks - Giménez, Roser; Queralt, Sheila (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Three homemade audiovisual recordings filmed a few days before the 2017 terrorist attacks to Barcelona and Cambrils by some individuals involved in these events were weighed as evidence during the trial held at the Audiencia Nacional between November, 10 2020, and May, 27 2021. No expert in linguistics analyzed this evidence in the proceedings. In Spain, the literature on jihadist terrorism has focused on the process of radicalization, including the use of digital media for this purpose and the importance of counter-narratives to battle it. However, few studies have analyzed terrorist productions from a linguistic perspective. This study examines the recordings screened in the trial for the 2017 attacks through the lens of the comprehensive model for pragmatic and discourse analysis put forward by Fuentes Rodríguez (2000, 2009). Results show how various linguistic devices perform multiple functions at the super-, macroand microstructural levels, allowing the participants to address various audiences and fulfill three communicative goals. Participants claim membership of a jihadist community and convey a message aimed, on the one hand, to intimidate the viewers they discursively construct as their opponents and, on the other, to obtain recognition from those that share their ideological stance. The discursive singularities of these recordings and their commonalities with productions linked to other forms of terrorism are discussed against the literature.